Complementary Nck1/2 Signaling in Podocytes Controls α Actinin-4–Mediated Actin Organization, Adhesion, and Basement Membrane Composition. Issue 8 (August 2022) - Martin, Claire E.; Phippen, Noah J.; Keyvani Chahi, Ava; Tilak, Manali; Banerjee, Sara L.; Lu, Peihua; New, Laura A.; Williamson, Casey R.; Platt, Mathew J.; Simpson, Jeremy A.; Krendel, Mira; Bisson, Nicolas; et al.
Significance Statement: Podocyte detachment is a major contributor to kidney disease progression, yet the mechanisms controlling podocyte adhesion are not well understood. We identified novel roles for Nck1 and Nck2 cytoskeletal adaptor proteins in cell adhesion through regulation of actin bundling at focal adhesions via α actinin-4. In vivo, loss of Nck1 and/or Nck2 increases basement membrane matrix deposition and renders podocytes more susceptible to damage after injury and with aging. More severe defects are observed with Nck2 deficiency, consistent with identification of distinct effector proteins. The results suggest an essential role for Nck adaptors as molecular hubs integrating multiple actin-based signals to control podocyte adhesion dynamics. Visual Abstract: Abstract : Background: Maintenance of the kidney filtration barrier requires coordinated interactions between podocytes and the underlying glomerular basement membrane (GBM). GBM ligands bind podocyte integrins, which triggers actin-based signaling events critical for adhesion. Nck1/2 adaptors have emerged as essential regulators of podocyte cytoskeletal dynamics. However, the precise signaling mechanisms mediated by Nck1/2 adaptors in podocytes remain to be fully elucidated. Methods: We generated podocytes deficient in Nck1 and Nck2 and used transcriptomic approaches to profile expression differences. Proteomic techniques identified specific binding partners for Nck1 and Nck2 in podocytes. We used cultured podocytes and mice deficient in Nck1 and/or Nck2, along with podocyte injury models, to comprehensively verify our findings. Results: Compound loss of Nck1/2 altered expression of genes involved in actin binding, cell adhesion, and extracellular matrix composition. Accordingly, Nck1/2-deficient podocytes showed defects in actin organization and cell adhesion in vitro, with podocyte detachment and altered GBM morphology present in vivo . We identified distinct interactomes for Nck1 and Nck2 and uncovered a mechanism by which Nck1 and Nck2 cooperate to regulate actin bundling at focal adhesions via α actinin-4. Furthermore, loss of Nck1 or Nck2 resulted in increased matrix deposition in vivo, with more prominent defects in Nck2-deficient mice, consistent with enhanced susceptibility to podocyte injury. Conclusion: These findings reveal distinct, yet complementary, roles for Nck proteins in regulating podocyte adhesion, controlling GBM composition, and sustaining filtration barrier integrity.